Room to maneuver in the middle: local elites, political action, and the state in India - Mitra, Subrata Kumar (World politics, 1991)
The intuitively plausible relationship between protest behavior and political instability is empirically supported by a large number of studies. Statistical evidence in support of this conjecture is provided by the correlation between indicators of protest behavior such as the presence of extremist parties and groups or the salience of an antisystem dimension and the rapid rise and fall of governments. The theories of writers such as Huntington, Gurr, and Davies suggest that when social and political mobility overtake the rate of economic growth, die result is radical challenge to the system by extremist parties and protest movements, leading to political instability and the loss of legitimacy. The main argument of this article is that the relationship between protest behavior and legitimacy may be more complicated than that, particularly when state responsiveness under the impact of popular protest and redistributive economic policies is seen as an intervening factor. By drawing on a survey of localelites in India, the article shows that certain forms of protest behavior, used in conjunction with conventional forms of participation such as contacting bureaucrats and political leaders at higher levels, might actually contribute to greater legitimacy of the state by providing an alternative channel of participation, extending the political agenda, and contributing to the recruitment of new and previously powerless social forces.
Published online by Cambridge University Press: 13 June 2011
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 21.06.2021
Keywords: Indien